1995
DOI: 10.4141/cjps95-022
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine ammonia lyase as a precursory enzyme of legume stem lignification

Abstract: la luzerne. Toutes espdces confondues, la teneur en lignine n'€tait pas positivement corrdlee avec I'activitd PAL exprim6e en fonction de la teneur en prot6ines, mais elle I'6tait quand I'activitd PAL 6tait exprimee par gramme de protdines (R-0,76 P < 0,05).De plus, calcul6e par plante individuelle, la teneur en lignine 6tait positivement corr6l6e avec PAL (r : 0,60 P < 0,05). I ressort de ces observations que I'activit6 de la PAL est relide avec I'accumulation de la lignine, dans une relation de cause Dr effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Both PAL transcript level and PAL activity decreased basipetally along the stem, indicating the maximum of both responses occur in actively-elongation internodes. Similar results were also reported by Morrison (1994) and Bidlack (1995). In this work, NaCl treatment of A.littoralis plants results in increased PAL protein that has been related to increament of lignin content and has been associated with reductions in stem growth.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both PAL transcript level and PAL activity decreased basipetally along the stem, indicating the maximum of both responses occur in actively-elongation internodes. Similar results were also reported by Morrison (1994) and Bidlack (1995). In this work, NaCl treatment of A.littoralis plants results in increased PAL protein that has been related to increament of lignin content and has been associated with reductions in stem growth.…”
Section: Discussionsupporting
confidence: 90%
“…is the first enzyme of phenylpropanoid pathway that catalyzes the conversion of L-phenylalanine to trans-cinnamic acid. Positive effect of PAL on plant cell wall lignification has been established (Bidlack et al, 1995) and Down regulation of PAL resulted in lignin modification in transgenic plants (Ogras et al, 2000). Studies have shown that PAL activity respond to various stresses, such as wounding, drought, salinity, heavy metals and infection by viruses, bacteria or fungi, therefore, PAL is involved in the defense response of plant cells (MacDonald andD Cunha, 2007, Gao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Lignin, an umbrella term for a large group of complex aromatic polymers resulting from the oxidative polymerization of hydroxycinnamyl alcohols ( 32 , 33 ), is associated with mechanical support, water transport in the xylem, and defense against pests and microorganisms in plants ( 34 ). In monocots, lignin deposition occurs after the incorporation of hemicellulose and cellulose into the cell wall ( 35 , 36 ). Lignification begins when cell wall polysaccharides become cross-linked to monolignols through hydroxycinnamic acids ( 37 ).…”
mentioning
confidence: 99%